The roles of partnering and boundary activities on project resilience under disruptions - Shen, Wenxin; Lim, Huey Wen; Fang, Dongping (Journal of Civil Engineering and Management, 2024)
Construction projects inevitably encounter adversities that threaten their functionality and performance. Understanding the enhancement of project resilience, especially in extreme situations like the COVID-19 pandemic, is crucial. This study introduces a theoretical model to explore how partnering and boundary activities among project stakeholders influence project resilience, and in turn, impact project performance. Based on data gathered from a questionnaire survey involving 172 construction projects in China, the results indicate that project resilience directly and positively affects project performance during the COVID-19 pandemic. Partnering and boundary activities emerge as primary determinants of project resilience. They not only directly impact project resilience and performance, but their impact on project resilience  also indirectly influences project performance. The findings offer valuable theoretical and practical insights into the improvement of project resilience through effective boundary activities and partnering.